Th1 and Th17 mucosal immune responses elicited by nasally inoculation in mice with virulence factors of Mycoplasma hyopneumoniae. (November 2022) - Xu, Lulu; Hao, Fei; Wang, Jingjing; Feng, Zhixin; Zhang, Lei; Yuan, Ting; Chen, Rong; Zhang, Zhenzhen; Shao, Guoqing; Xiong, Qiyan; Lin, Johnson; Xie, Xing; et al.
Abstract: Nicotinamide Adenine Dinucleotide-Dependent (NADH) flavin oxidoreductase and NADH oxidase (NOX) are important virulence factors of Mycoplasma hyopneumoniae (Mhp), which are devoted to the function of adhesion, oxidative stress damage and apoptosis to host cells in our previous studies. Here, immune responses of NADH flavin oxidoreductase (NFOR) and NOX in mice and immune efficacy inoculated with intramuscular (IM), intranasal (IN), intramuscular unite intranasal (IM + IN) approaches were evaluated and compared. Cellular immunity levels, systemic immune and local mucosal immune responses were investigated by indirect enzyme-linked immunosorbent assay (iELISA) and quantitative reverse transcription PCR (qRT-PCR). Mice inoculated with NFOR and NOX by IM and IN or IM + IN could induce obvious secretion of specific immunoglobulin G (IgG) and secretory immunoglobulin A antibodies (sIgA) compared to those in negative control group. IM + IN inoculation resulted in systemic and local mucosal immune responses that were strongly produced. Moreover, Mhp NFOR and NOX could activate local mucosal immune responses mediated by Th1 and Th17 cells by IN. Our finding supported the notion that IM + IN was an effective immunization route for Mhp, which lays a foundation for more effective prevention of Mhp, and provides theoretical basis for the development of new subunit vaccines of Mhp. Highlights: NFOR and NOX are two new virulence factors of Mhp. NFOR and NOX could induce humoral and local mucosal immune responses. Intranasally immunized with NFOR and NOX could activate Th1 and Th17 immune responses in mice. IM + IN route could be used as an optimized immunization method for vaccine development of Mhp.